Acceptance and Use of Information Technology: Understanding Information Systems for Indonesia’s Humanitarian Relief Operations - Made Irma Dwiputranti; Raden Adriyani Oktora; Liane Okdinawati; Mohamad Nurkamal Fauzan (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2019)
Disaster management includes distributing logistical assistance to disaster victims. The implementation of this distribution must occur at the right time, at an appropriate location, on target and be appropriate to the needs of the victims. This research aims to design an information system to improve the performance of disaster relief operations by managing the information while monitoring and evaluating humanitarian relief operations.Consequently, understanding the primary determinants of user acceptance behavior has become a vital aspect in the successful implementation of the information system. The Unified Theory of Acceptance and Use of Technology (UTAUT) model is a tool to investigate and give a better understanding of the factors that affect the potential users’ acceptance and use of an information system. This research used 131 different informants from different groups of potential users to measure performance expectancy, effort expectancy, social influence, and facilitating conditions. The results have shown strong relationships between four aspects of the measurements for the acceptance of all parties involved in humanitarian relief operations.